PENGARUH BAURAN PEMASARAN JASA TERHADAP PEMBELIAN PRODUK ASURANSI PADA PT. PRUDENTIAL LIFE ASSURANCE AREA JAKARTA - Muslim A.Madjid (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
This study discusses studying the marketing mix of the decision to purchase insurance products at PT. Prudential Life Assurance Area Jakarta and to find information about marketing based on simultaneous decisions on purchasing insurance products at PT. Prudential Life Assurance Area Jakarta and find out the very dominant variable on the decision to purchase insurance products at PT. Prudential Life Assurance Area Jakarta. The analytical method used in this research is to use the multiple regression analysis method. The results showed that the product, price, promotion, people, and process variables together and also partially had a significant influence on purchasing decisions for Prudencial products in Jakarta. The dominant dominant variable in the purchase decision is the price and promotion variable.